KEARIFAN LOKAL BUGIS DALAM AL-QUR’AN: TELAAH MAKNA “DUAMI KUALA SAPPO, UNGANNA PANASAE NA BELONA KANUKUE” - Latif, Abdul; Rifa'in, Aswar (TAFASIR: Journal of Quranic Studies, 2025)
This article discusses the relationship between the local wisdom of the Bugis community, particularly the traditional advice (pappaseng ogi) "duami kuala sappo, unganna panasae na belona kalukue", and the values contained in the Qur’an. Using a qualitative-descriptive approach and the contextual hermeneutics method, this study reveals the symbolic and ethical meanings of the expression and its connection to the concepts of honesty, steadfastness (istiqamah), purity, and cleanliness in Islamic teachings. It is hoped that the results of this research can strengthen the synergy between local wisdom and the universal values of Islam in shaping a society with honest and clean character in their way of life.  Keywords: (Local wisdom, Bugis, Qur’an, ethical values, steadfastness, Islamic culture)